John Locke as translator - Yolton, J (Voltaire Foundation, 2017)
Pierre Nicole was a major figure in the Jansenist controversy in seventeenth-century France. His essays, which were widely read and appeared in various editions during his lifetime, cover a broad range of religious subjects. John Locke first came across Nicole’s work during his visit to France in the 1670s, and was so struck by it that he intended to translate all the Essais de morale into English. When he had translated three of them, however he learned that the work had been done already, so he abandonned the project and presented what he had done so far to the countess of Shaftesbury, wife of his patron. Locke’s translation, in a neatly written presentation copy, is now housed in the Pierpont Morgan Library in New-York. The three essays that he translated – ‘Discours (…) de l’existence de Dieu & l’immortalité de l’âme’, ‘Traité de la faiblesse de l’homme’, and ‘Traité des moyens de conserver la paix avec les hommes’ – deal with topics that he later discusses at length in his own writings: society, morality, toleration and opinion. This volume reproduces the text of Nicole’s three essays from an early edition facing Locke’s deliberately free and impressionistic rendering into English, a style which he hoped might convey th sense of the author better than a literal translation. The choice of these three essays to translate first, out of the whole of the Essais de morale, and the changes that Locke made to his French original in the course of translation, illuminate our understanding of his thought and of its development. Foreword by John W.Yolton Acknowledgements Editorial conventions Abbreviations Introduction Discourses, by Pierre Nicole, translated by John Locke Dedication to the Countess of Shaftesbury Bibliography Index